Temporal changes of Sall4 lineage contribution in developing embryos and the contribution of Sall4-lineages to postnatal germ cells in mice. Issue 1 (December 2018) - Tahara, Naoyuki; Kawakami, Hiroko; Zhang, Teng; Zarkower, David; Kawakami, Yasuhiko
Abstract Mutations in theSALL4 gene cause human syndromes with defects in multiple organs.Sall4 expression declines rapidly in post-gastrulation mouse embryos, and our understanding of the requirement ofSall4 in animal development is still limited. To assess the contributions ofSall4 expressing cells to developing mouse embryos, we monitored temporal changes of the contribution ofSall4 lineages using aSall4 GFP-CreER T2 knock-in mouse line and recombination-dependent reporter lines. By administering tamoxifen at various time points we observed that the contributions ofSall4 lineages to the axial level were rapidly restricted from the entire body to the posterior part of the body. The contribution to forelimbs, hindlimbs, craniofacial structures and external genitalia also declined after gastrulation with different temporal dynamics. We also detectedSall4 lineage contributions to the extra-embryonic tissues, such as the yolk sac and umbilical cord, in a temporal manner. TheseSall4 lineage contributions provide insights into potential roles ofSall4 during mammalian embryonic development. In postnatal males, long-term lineage tracing detectedSall4 lineage contributions to the spermatogonial stem cell pool during spermatogenesis. TheSall4 GFP-CreER T2 line can serve as a tool to monitor spatial-temporal contributions ofSall4 lineages as well as to perform gene manipulations inSall4 -expressing lineages.